Does evaluator experience have an impact on the diagnosis of lumbar spine instability in dynamic MRI? Interobserver agreement study. Issue 3 (June 2015) - Patriarca, Lucia; Letteriello, Mayla; Di Cesare, Ernesto; Barile, Antonio; Gallucci, Massimo; Splendiani, Alessandra
Objectives: We aimed to evaluate interobserver agreement in the definition of spine instability among spine neuroradiologists with or without experience in dynamic magnetic resonance imaging (MRI). Material and methods: Two expert neuroradiologists and two residents retrospectively evaluated the pre-operative dynamic MRI examinations of patients with vertebral instability. Segmental motion, defined as excessive (more than 3 mm) translational motion from supine to upright, was investigated in 103 subjects (309 segments) using kinetic MRI. Radiographic parameters which can help indicate segmental instability include disc degeneration, facet joint osteoarthritis, and ligament flavum hypertrophy. These three radiographic parameters were simultaneously evaluated, and the combinations corresponding to significant segmental instability at each level were determined. The agreement among the neuroradiologists was calculated using the kappa coefficient. All patients had neurosurgical intervention to stabilize the spine. Results: Agreement was high among experienced and non-experienced neuroradiologists. Agreement was nearly perfect for spinal location of spinal instability. Conclusions: This study demonstrates that the experience of the evaluator has a low impact on the assessment of spinal instability if correct classification is used. The interobserver agreement confirms the usefulness and safety of kinetic MRI in the correct diagnosis of spinal instability even by less experienced evaluators.